Kebertahanan Seni Tari Legong Ratu Dedari Terhadap Pengembangan Kesenian di Desa Ketewel - Indra Putra, I Komang; Suarsana, I Nyoman; Kaler, I Ketut (Sunari Penjor : Journal of Anthropology; Vol 4 No 1 (2020), 2021)
The persistence of Legong Ratu Dedari Dance in Ketewel Village is very well known as a classical Balinese dance group that has very complex movements and the accompanying percussion is the influence of Gambuh. In its preservation, the uniqueness of this dance can be seen in its very sacred performances and wearing masks during its performance. The purpose of this research is to find out how the development process of Legong Ratu Dedari Dance in the Globalization Era. The results of the study explain the persistence of the Legong Ratu Dedari dance, which is a sacred and unique type of dance because there are several angel masks that are characteristic of classical dance in Ketewel Village. The Legong Ratu Dedari dance is the most famous legong dance before the creation of other legong dances in Bali. As for the development of the Legong Ratu Dedari Dance, there is a special social organization formed by Ketewel Village, namely the Indra Parwati Organization. The organization was formed from a group of young people and girls in Ketewel Village, as a special organization in preserving and maintaining the sustainability of the Legong Ratu Dedari Dance. Indra Parwati's organization educates and looks for a girl who is not menstruating so that she can dance the legong dance. In this effort, it can save and preserve the typical culture of Ketewel Village to become more developed and beneficial for the welfare of the Ketewel Village community.